Audit committee, board of director characteristics and financial reporting quality - ZHU, HUIXIAN (2017)
This study examines whether audit committees and board of director characteristics are related to financial reporting quality. In this study, earnings management as one of the factors of financial reporting quality, is chosen to represent the quality of financial reporting. The earnings management in this study is proxied by abnormal accruals. In this study, board characteristics including board independence, board size, board duality and board meeting frequency are chosen to test the impacts on abnormal accruals. Audit committees characteristics including audit committee independence and audit committee financial expert are chosen to test whether they have impacts on abnormal accruals. The study is going to research companies in the UK, so the data is chosen from Financial Times Stock Exchange 100 Index (FTSE 100). As this study aims to research the recent years’ results, the most recent available data from 2014 to 2015 is used. There are 198 firm-year observations with available data to calculate the abnormal accruals which are the indicators of financial reporting quality. The data of independent variables is collected from the Datastream and some variables are collected from the financial statements of the sample companies. The results of the regression in this study are that board duality, board meeting frequency, firm size, loss and cash flow are significantly related to abnormal accruals. Board duality is negatively related to abnormal accruals. Board meeting frequency is also negatively related to abnormal accruals. These results suggest that a company without board duality may have higher financial reporting quality than that with board duality, and the more frequently board of directors meet, the less abnormal accruals are, which will results in higher financial reporting quality. On the other hand, the control variables including firm size, loss and cash flow are all negatively related to abnormal accruals as well.